Economic analysis in health care - Morris, S. [ (Stephen)] , 1971- (John Wiley & Sons, 2012)
Economic analysis in health care, second edition is intended as a core textbook for advanced undergraduate and postgraduate students of health economics. The authors provide comprehensive coverage of the field of economics in health care and the evaluation of health care technologies